Plastic shrinkage cracking of fiber reinforced concrete - Eren, Özgür; Abdalkader, Ashraf (My University, 2006)
The main objective of this study was to investigate the effect of fiber volume (i.e control, 0.5%, 1.0%, and 1.5%) and aspect ratios of 55, 65, and 80 of hooked-end steel fibers on the behaviour of plastic shrinkage cracking during the first few hours after mixing. Properties such as compressive strength, splitting tensile strength, VeBe time and wet density were investigated. During this research two different strength levels (56 and 73 MPa at 28 days) were studied. The following relations are obtained (a) Plastic shrinkage versus fiber volume, (b) Plastic shrinkage versus fiber aspect ratio, (c) Plastic shrinkage versus strength level. The results indicated that the total plastic shrinkage crack area and maximum plastic shrinkage crack width are significantly reduced with the addition of steel fibers. Fiber content of 1.5% with aspect ratio of 80 resulted in a 74% and 70% reduction in total crack area and maximum crack width, respectively compared to plain concrete without fiber. © 2006 by School of Engineering and Technology, Asian Institute of Technology.
10th East Asia-Pacific Conference on Structural Engineering and Construction, EASEC 2010 --
Keywords: Compressive strength; Fiber reinforced concrete; Plastic shrinkage cracking; Splitting tensile; Steel fibers; Superplasticizer; VeBe time